Anti-inflammatory, analgesic, antioxidant, and alpha-amylase inhibitory effects of the hydroethanolic leaf extract of Aleuritopteris bicolor (Roxb.) Fraser-Jenk. - Prabhat Kumar Jha; Bipindra Pandey; Ram Kishor Yadav; K. C. Sindhu; Sandesh Poudel; Sushil Panta (PLoS ONE, 2025)
Aleuritopteris bicolor (Roxb.) Fraser-Jenk. is used in traditional medicine in Nepal to treat a variety of ailments. This study aimed to investigate qualitative phytochemical screening, quantitative phytochemical analysis (total phenolic and flavonoid content estimation), in vitro antioxidant activity, alpha-amylase inhibitory activity of Aleuritopteris bicolor (Roxb.) Fraser-Jenk. leaves from Nepal. Furthermore, this study examined the analgesic (tail flick and hot plate test method) and anti-inflammatory (carrageenan-induced paw edema) activities of Aleuritopteris bicolor leaves in an acute pain and inflammation rat model. The Aleuritopteris bicolor extract exhibited flavonoid (405.95 ± 0.28 mg QE/g) and phenolic content (20.98 ± 0.20 mg GAE/g). Aleuritopteris bicolor showed free radical scavenging activity with IC50 value in difference antioxidant methods (IC50:9.87 µg/mL, DPPH scavenging assay; 249.59 µg/mL, Hydrogen peroxide; 72.98 µg/mL, Nitric oxide assay), and significant Ferric reducing power assay (0.51 ± 0.004). It increased analgesic activity by 38.89% (hot plate test) and 16.84% (tail-flick test) at 250 mg/kg, reduced inflammation by 36.44% at 180 min (500 mg/kg), and inhibited alpha-amylase activity (IC50:59.31 µg/mL). Aleuritopteris bicolor exhibits significant analgesic, anti-inflammatory, and hypoglycemic potential, making it a promising candidate for further pharmacological exploration. This study marks the first scientific study of the in vivo analgesic and anti-inflammatory effects from the leaf extract of Aleuritopteris bicolor till date.